Deposition of Ti-C-N hard film by ion plating. Ion plating ni yoru Ti-C-N koshitsu himaku keisei - "Kuwano, S"; "Otake, T"; "Mano, T [Shizuoka Industrial Research Institute of Shizuoka Prefecture, Shizuoka (Japan)]" (1991)
It was attempted to develop a new film having characteristics of each of TiN and TiC by an activated reactive evaporation(ARE) process, a kind of ion plating. That is, a Ti-C-N film was formed by using titanium as evaporative source and nitrogen and acetylene gas as reactive gas. In the preliminary test for the deposition of the Ti-C-N film, a TiN film of Hv1600 was obtained. The conditions for depositing this film were as follows; electron gun output 10kV-175mA, Nsub 2 gas pressure 1{times}10{sup {minus}4}Torr, substrate heating temperature 400 centigrade, and substrate voltage 0.2kV. When the deposition of the Ti-C-N film was tried by mixing Csub 2Hsub 2gas under the same conditions, hardness of the film decreased to around Hv1100-1300. As a result of the evaluation of physical properties of this film, it was found that crystallinity of the film was getting worse with the increasing ratio of mixed Csub 2Hsub 2 gas. It was thus recognized that the reaction of Csub 2Hsub 2 gas was not proceeded efficiently. 4 refs., 8 figs.
Keywords: "36 MATERIALS SCIENCE"; "CHEMICAL VAPOR DEPOSITION"; "CHEMICAL ACTIVATION"; "COATINGS"; "CARBON ADDITIONS"; "NITROGEN ADDITIONS"; "TITANIUM ADDITIONS"; "VAPOR PLATING"; "ION BEAMS"; "ACETYLENE"; "CRYSTALLIZATION"; "ELECTRON GUNS"; "MIXING RATIO"; "PHYSICAL PROPERTIES"; "SUBSTRATES"; "VICKERS HARDNESS"; "ALKYNES"; "ALLOYS"; "BEAMS"; "CHEMICAL COATING"; "DEPOSITION"; "HYDROCARBONS"; "ORGANIC COMPOUNDS"; "PHASE TRANSFORMATIONS"; "PLATING"; "SURFACE COATING"; "TITANIUM ALLOYS"; "360101* - Metals & Alloys- Preparation & Fabrication"